Patient‐reported outcomes are worse for progressive‐onset multiple sclerosis than relapse‐onset multiple sclerosis, particularly early in the disease process. (24th September 2018) - Zhang, Y.; Taylor, B. V.; Simpson, S.; Blizzard, L.; van der Mei, I.
Abstract : Background and purpose: Treatments for progressive‐onset multiple sclerosis (MS) are lacking. To improve the disease management for progressive‐onset MS, the differences between relapse‐onset MS and progressive‐onset MS in patient‐reported disability, progression and symptoms were examined. Methods: A total of 1985 participants of the Australian Multiple Sclerosis Longitudinal Study were included. Associations between onset type and outcomes were assessed with negative binomial regression. Results: The severity of 17 of the 19 outcomes was significantly higher for progressive‐onset MS patients than relapse‐onset MS patients, including perspectives from disability, progression over the last year, fatigue, sensory, walking difficulties, pain, balance, spasticity, sexual dysfunction, bladder, bowel, anxiety, depression and the European quality of life (EQ‐5D) ( P < 0.05; adjusted mean ratio ranged from 1.11 to 1.52). The differences between the two onset types were most pronounced early in the disease process and reduced with increasing MS duration, and the interaction was significant for disability, progression over the last year, walking difficulties, bladder problems, bowel problems and spasticity. Conclusion: Participants with progressive‐onset MS were significantly worse off on nearly all patient‐reported outcomes than relapse‐onset MS participants, and the differences were most pronounced early in the disease course, highlighting the importance of early intervention for those with progressive‐onset MS.